The Crime of Spreading Pornographic Content in Digital Media - Nugroho, Muhamad Rizal Satrio; Alhadi, Muhammad Nurcholis; Muslim, Ikhwanul (Faculty of Law, Universitas Pattimura, 2025)
Introduction: As technology continues to advance, it brings significant changes to people’s lives. However, these advancements are also accompanied by threats, one of which is cybercrime. A particular form of this crime is the dissemination of pornographic content, which has substantial negative impacts, both on individual victims and on society as a whole.Purposes of the Research: This study aims to examine the legal regulations in Indonesia governing the dissemination of pornographic content and to analyze the legal protection for victims as stipulated in Law Number 12 of 2022 concerning Sexual Violence Crimes.Methods of the Research: The research method used is normative juridical approach, involving an analysis of relevant laws, such as the Criminal Code, the Electronic Information and Transactions Law, the Pornography Law, and the Law on Sexual Violence Crimes.Findings of the Research: The results of the study show that the dissemination of pornographic content is regulated in articles 282, 296, and 50 of the Criminal Code, as well as Article 27 paragraph (1) and Article 45 paragraph (1) of the Electronic Information and Transaction Law, with strict criminal threats. The Pornography Law and Law Number 1 of 2024 strengthen supervision of electronic systems and administrative sanctions. The Sexual Violence Crime Act provides comprehensive protections for victims, including the right to legal services, psychological support, content removal, and protection from perpetrator threats and lawsuits.